Arabidopsis CaM binding protein CBP60g contributes to MAMP-induced SA accumulation and is involved in disease resistance against Pseudomonas syringae. - Lin Wang (Public Library of Science (PLoS), 2009)
Salicylic acid (SA)-induced defense responses are important factors during effector triggered immunity and microbe-associated molecular pattern (MAMP)-induced immunity in plants. This article presents evidence that a member of the Arabidopsis CBP60 gene family, CBP60g, contributes to MAMP-triggered SA accumulation. CBP60g is inducible by both pathogen and MAMP treatments. Pseudomonas syringae growth is enhanced in cbp60g mutants. Expression profiles of a cbp60g mutant after MAMP treatment are similar to those of sid2 and pad4, suggesting a defect in SA signaling. Accordingly, cbp60g mutants accumulate less SA when treated with the MAMP flg22 or a P. syringae hrcC strain that activates MAMP signaling. MAMP-induced production of reactive oxygen species and callose deposition are unaffected in cbp60g mutants. CBP60g is a calmodulin-binding protein with a calmodulin-binding domain located near the N-terminus. Calmodulin binding is dependent on Ca(2+). Mutations in CBP60g that abolish calmodulin binding prevent complementation of the SA production and bacterial growth defects of cbp60g mutants, indicating that calmodulin binding is essential for the function of CBP60g in defense signaling. These studies show that CBP60g constitutes a Ca(2+) link between MAMP recognition and SA accumulation that is important for resistance to P. syringae.